2005
DOI: 10.1126/science.1106036
|View full text |Cite
|
Sign up to set email alerts
|

Escape of Intracellular Shigella from Autophagy

Abstract: The degradation of undesirable cellular components or organelles, including invading microbes, by autophagy is crucial for cell survival. Here, Shigella, an invasive bacteria, was found to be able to escape autophagy by secreting IcsB by means of the type III secretion system. Mutant bacteria lacking IcsB were trapped by autophagy during multiplication within the host cells. IcsB did not directly inhibit autophagy. Rather, Shigella VirG, a protein required for intracellular actin-based motility, induced autoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
778
3
8

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 785 publications
(803 citation statements)
references
References 17 publications
14
778
3
8
Order By: Relevance
“…[44][45][46] Autophagy has an important role in physiological and pathological processes, such as degradation of cytoplasmic components, cellular response to nutrient starvation and apoptosis. 47,48 Moreover, autophagy is also relevant in innate 49,50 and adaptive immunity. 51,52 Atg16l in conjunction with an Atg12-Atg5 conjugate, has a crucial role in the elongation of isolation membranes and the initial step of autophagosome formation, 53 and it is essential in the targeting and destruction of pathogens 49 as well as in foreign (microbial) antigen processing and presentation 52 protecting against viruses, bacteria and other pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…[44][45][46] Autophagy has an important role in physiological and pathological processes, such as degradation of cytoplasmic components, cellular response to nutrient starvation and apoptosis. 47,48 Moreover, autophagy is also relevant in innate 49,50 and adaptive immunity. 51,52 Atg16l in conjunction with an Atg12-Atg5 conjugate, has a crucial role in the elongation of isolation membranes and the initial step of autophagosome formation, 53 and it is essential in the targeting and destruction of pathogens 49 as well as in foreign (microbial) antigen processing and presentation 52 protecting against viruses, bacteria and other pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Over 30 ATG genes have been identified in yeast and at least 11 (ATG 1,3,4,5,6,7,8,9,10,12 and 16) have orthologs in mammals, Atg6 is also known as Beclin1 and Atg8 is commonly called LC3 in mammals. Not surprisingly given the large number of stimuli that modulate autophagy, numerous upstream signaling pathways (growth factor signaling, PI3 kinase/ Akt, MAP kinases, AMP dependent protein kinase, small GTPases, trimeric G proteins, inositol triphosphates, calcium signaling and others) regulate the process.…”
Section: Regulation Of Autophagymentioning
confidence: 99%
“…Autophagy is a mechanism by which organelles are removed and is the primary degradation mechanism for long-lived proteins and thus maintains quality control for proteins and organelles. Autophagy is ubiquitous in eukaryotic cells and important in development and in diverse pathophysiological conditions (5)-for example providing protection against neurodegeneration (6,7), infections (8,9) and tumor development (10)(11)(12)(13). Cells that are deficient in autophagy also demonstrate enhanced chromosomal instability (14,15), which may be related to the tumorigenesis associated with autophagy deficiency.…”
mentioning
confidence: 99%
“…A similar phenomenon is observed in cells infected with Shigella. 29 However, Shigella may be more clever, because it is able to escape from autophagy. A Shigella mutant lacking the secretory protein IcsB is defective in multiplication within host cells.…”
Section: Degradation Of Invading Bacteriamentioning
confidence: 99%
“…A Shigella mutant lacking the secretory protein IcsB is defective in multiplication within host cells. Ogawa et al 29 reported that the icsB mutant is sequestered by autophagosome-like structures. In contrast, wild-type Shigella evades autophagy by secreting IcsB.…”
Section: Degradation Of Invading Bacteriamentioning
confidence: 99%